The Role of Organizational Behavior of the Ministry of Sports and Youth in International Military Sports Events - Ordookhani , Hooman; Tojari, Farshad; Nikaeen , Zinat (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The purpose of this study was to investigate the role of the organizational behavior of the Ministry of Sports and Youth in international military sports events. Methodology: This research is qualitative-exploratory in strategy, with the qualitative sample including athletes involved in CISM sports events, sports event coaches, and senior officials, totaling 20 individuals. The research tools consisted of researcher-developed coding sheets, and interviews were conducted with participants using the oral history method. Findings: The results revealed that the categories derived from the interviews with the participants in the study were identified in the form of 26 categories and 90 conceptual codes. These were embedded within the six dimensions of the paradigmatic model, which includes causal conditions (4 categories and 24 concepts), the central and core category (3 categories and 10 concepts), strategies (3 categories and 10 concepts), contextual conditions (8 categories and 18 concepts), intervening or mediating conditions (4 categories and 18 concepts), and outcomes (4 categories and 10 concepts). Conclusion: Based on the research findings, the quality enhancement of hosting CISM events faces numerous limitations. To mitigate the impact of these limitations, strategies such as developing and strengthening internal and international communications, particularly with the Ministry of Sports and Youth and other Islamic countries, and optimally utilizing existing potentials to maintain and elevate the status of military sports can be proposed.